THE EFFECT OF ORAL VITAMIN D ON TUMOR NECROSIS FACTOR-? EXPRESSION IN TRABECULAR MESHWORK OF WISTAR GLAUCOMA MODEL: Oral Presentation - Experimental Study - Resident - Hendriati; ERINA, RIKHA; Ariesti, Andrini (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesElevated intraocular pressure (IOP) is a risk factor for the development and progression of glaucomathat can induces inflammation in the trabecular meshwork through the production of proinflammatorycytokines such as TNF-?. Inflammation induce mechanical stress and changes in theextracellular matrix in the trabecular meshwork, resulting in hypertonicity and resistance toaqueous humor outflow. Vitamin D can modulate cytokine production by suppressing TH1 cellexpression and inducing TH2 cell expression. The production of pro-inflammatory cytokines can besuppressed by the presence of vitamin D. MethodsAn experimental study of 30 wistar glaucoma model were divided into 3 groups, non treatmentgroup ( A and B) and the oral vitamin D (1200 IU/kg/day) group (C) for 14 days. TNF-? expressionsin trabecular meshwork were measured by immunohistochemical staining. Group A was measuredon day 3, while group B and C were measured on day 14. The differences between the three groupswere analyzed statistically using one way ANOVA test. Significantly different if the p<0.05. ResultsThe mean expression of TNF- ? in the trabecular meshwork of wistar glaucoma model in group A, B,and C was 22,2 ± 2,51%, 39,1 ± 3.98%, 34.2 ± 3,19 % respectively. There was significantlydifference in TNF-? expressions between the three groups (p<0.001). ConclusionVitamin D per oral can decrease TNF-? expression in the trabecular meshwork of wistar glaucomamodel on day 14 . Studies in wistar and humans are still needed to assess the effect of vitamin D onothers pro-inflammatory cytokines in glaucoma.